2008
DOI: 10.1109/jmems.2008.2007227
|View full text |Cite
|
Sign up to set email alerts
|

Schottky Barrier Contact-Based RF MEMS Switch

Abstract: This paper presents the design, fabrication, and measurement results for a novel Schottky barrier contact-based radio frequency (RF) microelectromechanical systems (MEMS) switch. This Schottky barrier contact allows one not only to operate the RF MEMS switch in a traditional capacitive mode when it is reverse biased but also conduct current in a forward biased state. Forward biasing the switch recombines trapped charges, thus extending the lifetime of the switch. This paper intimately combines MEMS processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The first step in characterizing the linearity is to 5. Functional diagram of the linearity testing setup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step in characterizing the linearity is to 5. Functional diagram of the linearity testing setup.…”
Section: Resultsmentioning
confidence: 99%
“…This work describes a method to control the dielectric conductivity by reverse biasing a Schottky baffier to minimize conductivity and forward biasing the Schottky barrier to flush out any trapped charge. Initial data indicates this switch has shown a 35% improvement in lifetime [5] and has the potential for much more. This Schottky barrier is integrated into the RF MEMS switch structure and doubles as the switch dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…Such switches were expected to have an operational lifetime that could be 10 3 to 10 9 times longer than the operational lifetime of comparable pre-existing switches that lack the textured surface. Finally, since the electrical properties of the amorphous dielectric films used in MEMS depend on the deposition conditions [15,16,35] and no standardization has been introduced on the deposition conditions, a different approach based on Schottky barrier contact was proposed in [35].…”
Section: Assessment On Mim Capacitorsmentioning
confidence: 99%
“…Although this technique does not entirely remove charge injection into the dielectric, extended test results have shown switches having higher reliability through this technique.Charging in RF-MEMS switches has been addressed by using a Schottky diode with a membrane and semiconductor in place of the usual dielectric layer. Pillans et al[37] have demonstrated the use of Schottky barrier contact based RF-MEMS switch. In this switch, n ++ InGaAs is used as the bottom electrode and epitaxial InAlAs is used as the dielectric layer.…”
mentioning
confidence: 99%